Total Antioxidant Status in Type 2 Diabetic Patients in Palestine - Akram T. Kharroubi; Hisham M. Darwish; Mutaz A. Akkawi; Abdelkareem A. Ashareef; Zaher A. Almasri; Khaldoun A. Bader; Umaiyeh M. Khammash (Journal of Diabetes Research)
The objective of this study was to compare the level of total antioxidant status (TAS) in type 2 diabetic and normal Palestinian subjects as well as the major factors influencing TAS levels. A sample of convenience composed of 212 type 2 diabetic and 208 normal subjects above the age of 40 were recruited. Only 9.8% of the subjects had normal body mass index (BMI) levels (<25), 29% were overweight (≥25 to <30), and 61.2% were obese (≥30). The mean levels of TAS were significantly higher in diabetic compared to control subjects (2.18 versus 1.84 mM Trolox, P = 0.001) and in hypertensive subjects compared to subjects with normal blood pressure (BP). Mean TAS levels were higher in obese compared to nonobese subjects (2.12 versus 1.85 mM Trolox, P = 0.001). Mean TAS levels were similarly higher in subjects with high fasting plasma glucose (FPG) compared to normal FPG (2.19 versus 1.90 mM Trolox) and high HbA1c (≥6.5%) compared to HbA1c < 6.5% (2.14 versus 1.91 mM Trolox). Multivariate analysis revealed that only diabetic status (P = 0.032) and the level of education (P = 0.036) were significantly associated with TAS. In conclusion diabetic patients had 18.5% increase in TAS levels compared to control subjects.